Effect of mixing banana stem juice and subsequent heating on rumen degradability of soy bean meal - Yulistiani, D; Puastuti, W; Mathius, I.W (Indonesian Journal of Animal and Veterinary Sciences, 2010)
The study was conducted to evaluate the rumen degradability of soy bean meal when it was mixed with banana stem juice and was subsequently heated. Banana stem juice was used as source of tanin to protect protein in soy bean meal from degradation in the rumen. The banana stem juice (in volume) was mixed with soy bean meal at three ratio, which were 1 : 1, 1:2 and 1 : 3 (w/v). These mixing was then heated at 60oC and 90oC. The heating was done in an oven. Sample from each treatment was then filled into polyester bag with porosity of 45 mm and the size of 5 x 9 cm. The bags were incubated in the rumen of fistulated sheep for 0, 2, 4, 8, 16, 24 and 48 hours. The experiment was carried out in factorial 3 x 2, with three levels of banana stem juice and 2 levels of heating and was arranged in completely randomized design. Untreated soy bean meal was also incubated used as control. Degradation data of dry matter and crude protein at each incubation time was fitted into exponential equation, P = a + b (1 - ect). Results shows that there was a significant interaction factor of stem juice ratio and heating on water soluble substrate (constant A) where heating at 90oC with ratio 1 : 2 (w/v) resulted in the highest a. The insoluble but fermentable substrate (B) was decreased by the increasing concentration of banana stem juice, while the rate of protein degradation of b fraction was lower compared to control. In conclusion, banana stem juice can reduce the rate of degradation of soy bean meal in the rumen. Key words: Degradation, Crude Protein, Soy Bean Meal, Banana Stem Juice